Use Of ICT In Arabic Language Education At High School Level And Its Relationship With Teacher Skills - Muhdi, Ali; Yuslam, Yuslam; Ngarifillaili, Nurul; Iqbal, Ali; Purnama, Yulian (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Nowadays, the use of ICT has become a demand for education. The use of ICT actually requires special skills, however, it is also necessary to use ICT in Arabic language education. The use of ICT in the Arabic language learning process can enable teaching staff to make various modifications that suit learning. With these conditions, teaching staff can train and increase the skills they have to be more creative in the learning process. This research aims to determine the influence of the use of ICT in Arabic language education at the high school level and its relationship with teacher skills. Apart from that, researchers can also dig deeper into the use of ICT in Arabic language education and its relationship with teacher skills. The method used in this research is quantitative methods. The results of data acquisition were obtained by researchers through distributing questionnaires. The distribution of the questionnaire was carried out online using Google Froom software. The results of this data collection will later be tested and processed again using the SPSS application. The results of this research show that the use of ICT in Arabic language education is very adequate for the current situation and conditions. Apart from being proficient in using Arabic, teaching staff are also able to further improve their skills in using ICT. As an Arabic language educator, of course you also have to be clever in using ICT as a supporting activity in the learning process in high school and above. Based on the research that has been conducted, researchers can conclude that the use of ICT in Arabic language education at the high school level is closely related to improving teachers' skills in using ICT. Therefore, as educators it is also important to pay attention to good strategies in using ICT, so that the learning process runs well.